La complementarità: riflessioni antropologiche sul suo fondamento e senso - Ascencio, Juan G. (Alpha omega, 2021)
On the basis of an adequate anthropology, which explores the relationship between the person and its dimensions, the article proposes a wide-ranging reflection on the essence and experience of complementarity between man and woman starting from inter-personality and sexuality understood as personal dimensions.